2019
DOI: 10.3389/fphys.2019.00826
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conduction System Remodeling in Streptozotocin-Induced Diabetes Mellitus Rat Heart

Abstract: Cardiovascular complications are common in type 1 diabetes mellitus (TIDM) and there is an increased risk of arrhythmias as a result of dysfunction of the cardiac conduction system (CCS). We have previously shown that, in vivo , there is a decrease in the heart rate and prolongation of the QRS complex in streptozotocin-induced type 1 diabetic rats indicating dysfunction of the CCS. The aim of this study was to investigate the function of the ex vivo CCS and key pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 72 publications
4
22
0
Order By: Relevance
“…Genes underlying familial and acquired sick sinus syndrome. Familial sick sinus syndrome has been linked to mutations in Hcn4 91 , and acquired sick sinus syndrome in ageing 92 , heart failure 93 , atrial fibrillation 94 , diabetes 95 , pulmonary hypertension 96 and even athletes 11 has been linked to a downregulation of Hcn4. If there is a day-night rhythm in Hcn4 (P = 0.072), this may impact sick sinus syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Genes underlying familial and acquired sick sinus syndrome. Familial sick sinus syndrome has been linked to mutations in Hcn4 91 , and acquired sick sinus syndrome in ageing 92 , heart failure 93 , atrial fibrillation 94 , diabetes 95 , pulmonary hypertension 96 and even athletes 11 has been linked to a downregulation of Hcn4. If there is a day-night rhythm in Hcn4 (P = 0.072), this may impact sick sinus syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a decrease of HCN was found in the atria of metabolic murine model of mitochondrial dysfunction [ 19 ] and in sinoatrial node of Goto-Kakizaki type 2 diabetic rats [ 39 ]. Importantly, HCN downregulation was reported also in pacemaker cells [ 20 ], in sinoatrial node [ 20 ] and whole cardiac conduction system [ 40 ] of rats with type 1 diabetes mellitus induced by STZ manifesting in lower intrinsic heart rate, a lengthened sinoatrial conduction time and rate-corrected maximal sinoatrial node recovery time in vivo as well as a longer cycle length in vitro [ 20 ]. Also, knock out mouse models lacking Hcn2 or Hcn4 channels exhibit sinoatrial heart disturbances without reports of ventricular electric abnormalities [ 8 , 9 ] suggesting different roles of HCN channels in ventricles.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al reported that the family Bacteroidaceae was dysregulated in a diabetic mouse model [38]. Previous studies have shown that the abundance levels of Lactobacillus and Allobaculum, bene cial bacteria that can directly protect intestinal barrier function, are reduced in diabetic animal models [39,40].…”
Section: Discussionmentioning
confidence: 99%